Hidrolisis Karbohidrat dari Sampah Sayur dan Buah dengan Katalisator H2so4 Encer Sebagai Bahan Baku Bioetanol - Doni Rahmat Wicakso; Agus Mirwan (Universitas Lambung Mangkurat, 2008)
Bio-ethanol is an alternative motor fuel which environmental friendly and renewable because it can be produced from plants containing sugar, starch, and cellulose. Generally, bio-ethanol production consists of hydrolysis process to produce sugar and fermentation process to produce ethanol. This research was to study process of carbohydrate hydrolysis of fruit and vegetable wastes by dilute sulfuric acid solution. The product of sugar solution was expected to be used as raw material of bioethanol production. The variable of experiment is temperature between 393 – 493 K. The experiment was run with 600 ml sulfuric acid 0,5 % (volume) and one hundred gram of polysaccharide waste in an autoclave. The autoclave was closed prefectly, heated and shaked. When it reached 373 K, the time was taken as zero and sample of about 10 ml was taken. After reached desired temperature, the temperature was kept constant. During the process, every 5 minutes, samples were taken and then be analyzed its sugar concentration by Fehling methods. The homogenous kinetics model of fist orde was used to study kinetics in this experiment.